De franske forskelle og det kætterske Sydfrankrig - Laffitte, Maryse (Religionsvidenskabeligt Tidsskrift, 1998)
<span style="font-size: 9pt; font-family: "Times New Roman"; mso-ansi-language: EN-GB; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: Shruti; mso-bidi-font-style: italic; mso-fareast-language: DA; mso-bidi-language: AR-SA;" lang="EN-GB">Modern France is as a whole a country of Catholic culture, despite the presence of other religions, in so far as Catholicism has managed to impose itself historically as a state religion. Nevertheless, France is divided into traditionally believing and non‑believing regions. The South of France was particularly heretic and constituted from the Middle Age to the Reformation a focus of religious and political resistance to the power of the Roman Church, the feudal lords, and the king of France. In the 12th and 13th centuries, Catharism, which can be considered an ‘exemplary’ heresy, impregnated the religion and culture of the Languedoc region and the county of Foix. The Cathar heresy was annihilated, but it is on this basis, which is also that of Catholicism, that Protestantism took root three centuries later.